Repeated-sprint and effort ability in rugby league players - Johnston, R. D.; Gabbett, T. J. (The Journal of Strength and Conditioning Research, 2011)
The aim of this study was to (a) investigate the influence of tackling on repeated-sprint performance; (b) determine whether repeated-sprint ability (RSA) and repeated-effort ability (REA) are 2 distinct qualities; and (c) assess the test-retest reliability of repeated-sprint and repeated-effort tests in rugby league. Twelve rugby league players performed a repeated-sprint (12 × 20-m sprints performed on a 20-second cycle) and a repeated-effort (12 × 20-m sprints with intermittent tackling, performed on a 20-second cycle) test 7 days apart. The test-retest reliability of these tests was also established. Heart rate and rating of perceived exertion were recorded throughout the tests. There was a significantly greater (p <= 0.05) and large effect size (ES) differences for total sprint time (ES = 1.19), average heart rate (ES = 1.64), peak heart rate (ES = 1.35), and perceived exertion (ES = 3.39) for the repeated-effort test compared with the repeated-sprint test. A large difference (ES = 1.02, p = 0.06) was detected for percentage decrement between the 2 tests. No significant relationship was found between the repeated-sprint and repeated-effort tests for any of the dependent variables. Both tests proved reliable, with total sprint time being the most reliable method of assessing performance. This study demonstrates that the addition of tackling significantly increases the physiological response to repeated-sprint exercise and reduces repeated-sprint performance in rugby league players. Furthermore, RSA and REA appear to be 2 distinct qualities that can be reliably assessed with total time being the most reliable measure of performance.